Optimal Operation of a Smart Multi-Energy Neighborhood - Ata, Mustafa; Erenoglu, Aye Kubra; Sengor, Ibrahim; Erdinc, Ozan; Tascikaraoglu, Akin; Catalao, Joao P. S. (IEEE, 2019)
Together with the increasing population and prosperity levels of the growing countries, the economic and technological developments and modernized lifestyles of the end users have increased their electrical, heating and cooling energy demands extraordinarily. These services are generally provided to the end users independently, which leads to considerable reductions in the system efficiencies. For the purpose of providing a decrease in the demands of the end users and to transfer the energy carriers to the end users in an integrated and more efficient way, the concept of multi energy systems (MESs) has emerged. MESs could be developed at a district level, a city level and lastly at a country level. In this paper, a smart neighborhood MES model is proposed with the aim of achieving cost optimization by mixed integer linear programming (MILP) based formulation considering a time-of-use (TOU) tariff. In order to testify the effectiveness of the proposed optimization algorithm, two different case studies are conducted by taking into account flexible energy production capability of different energy carriers.
Keywords: Multi energy system; mixed-integer linear programming; optimization; system modelling; smart neighborhood; OPTIMAL POWER-FLOW; DISTRIBUTED MULTIGENERATION; ENERGY; SYSTEM; CCHP; Energy & Fuels; Engineering